GEOCHEMICAL FEATURES OF OIL AND THE ORIGIN OF OIL FIELDS - Marakushev A.A.; Pisotskii B.I.; Paneyakh N.A.; Gottikh R.P. (My University, 2004)
This article considers the parageneses of microelements in oil fields, which are largely represented by the following metals: Ni, Cu, Cr, Pt, Pd, Ru, Rh, and Ir. Samples were taken from 46 oil fields localized in Riphean to Neogene rocks at a depth interval of 840-4800 m and related to eight petroliferous provinces. The considered geochemical correlations serve as evidence in favor of the origin of oil fields in the framework of the Earth's endogenic activity stimulated by pulses of degassing of its liquid core. The discrete nature of this activity in the geological history is recorded by trap rocks, glaciation periods, biotic crises, diastrophic periods, and so on. The formation of oil fields is not an exception in this respect. Thus, the formation and geochemical signature of oil-forming fluids are directly related to the structure of the petroliferous provinces, the age of their basement, the thickness of consolidated crust and sedimentary cover, and the type and intensity of magmatic activity, i.e., the character of the geodynamic evolution of the lithosphere.